Using Collective Intelligence to identify barriers to implementing and sustaining effective Fundamental Movement Skill interventions: A rationale and application example. Issue 6 (19th March 2021) - Ma, Jiani; Hogan, Michael J.; Eyre, Emma L.J.; Lander, Natalie; Barnett, Lisa M; Duncan, Michael J.
ABSTRACT: To have population-level impact, interventions must be effectively implemented and sustained under real-world conditions. Few Fundamental Movement Skill (FMS) interventions are implemented at scale, and even fewer are sustained in a way that allows for ongoing evaluation. There has been increasing recognition of applying systems thinking to investigate the multitude of influences on interventions. To improve research-practice translations, investigations need to incorporate synthesised perspective and collective input from intervention stakeholders. This study trials Collective Intelligence (CI) – an applied systems science approach – to understand barriers to the adoption, implementation and institutionalisation of effective FMS interventions for children and adolescents. A total of 58 barriers were generated and organised into 13 barrier categories. Participants voted to select 10 critical barriers and generated a structural map among the barriers to guide future action mapping. Barriers related to Government and Institutional factors and Curricular Conflicts were structured as fundamental drivers of the system of barriers. By presenting this application example, we aim to underline the considerations and alleviate barriers to conducting much needed implementation and sustainability studies in FMS interventions. CI also adds to the "tool box" to understand the complexity and functioning of public health interventions, such as those targeting physical activity behaviours.